Cover Feature: In Situ Synthesis of Manganese Oxide as an Oxygen‐Evolving Catalyst: A New Strategy (Chem. Eur. J. 4/2021). Issue 4 (12th November 2020) - Abdi, Zahra; Bagheri, Robabeh; Reza Mohammadi, Mohammad; Song, Zhenlun; Görlin, Mikaela; Dau, Holger; Najafpour, Mohammad Mahdi
Abstract : So far, all studies on oxygen‐evolution reactions using Mn oxides in the presence of cerium(IV) ammonium nitrate (CAN) have been carried out by synthesizing Mn oxides in the first step, followed by the investigation of the Mn oxides in the presence of oxidants for the oxygen‐evolution reaction (OER). This work presents a case study of a new and promising strategy for in situ catalyst synthesis by adding Mn II to a CAN solution, resulting in the formation of Mn‐based catalysts for OER. More information can be found in the Full Paper by M. Görlin, M. M. Najafpour, et al. on page 1330 .